PRINCIPLES OF INTERNATIONAL LAW: CONCEPTUAL AND SUBSTANTIVE PROBLEMS - A. Kh. Abashidze (Московский журнал международного права, 2018)
Introduction. Taking into account the fact that neither the normative nor the doctrinal form contains an exhaustive list of principles of international law, clarification of the issues of their concept and content problems is important not only for international law itself and its adequate understanding, but also for application of law at the national level, because the national legal systems of states, including the Russian Federation, are widely based on the principles of international law. This article deals with theoretical and practical issues related to the principles of international law, and the study is not limited to the framework of international law, but also covers other general theoretical aspects of law, as well as non-normative aspects. The article contains the main thesis of the speech of prof. Aslan Abashidze addressed the judges of the Supreme Court of the Russian Federation, held at the invitation of the guidance of the Supreme Court of the Russian Federation on November 23, 2017.Materials and methods. The study is based on a considerable amount of materials, including international legal acts, decisions of international judicial institutions, national legislation of the Russian Federation and decisions of the highest judicial bodies of the Russian Federation, as well as classical and contemporary doctrinal studies of Russian and foreign authors. The methodological basis of the research was the general scientific methods (logical and system analysis, the dialectical method, methods of deduction and induction) and special methods of cognition (historical and legal, comparative legal and formal legal methods, method of legal modeling and forecasting).Research results. On the basis of the study of the doctrinal positions of Russian and foreign authors, international legal acts and practice of international judicial institutions, as well as national legislation of the Russian Federation and the national court practice of the Russian Federation concerning the principles of international law, the author makes conclusions on the conceptual and substantive problems concerning the principles of international law.Discussion and conclusions. In the article the author analyzes various approaches to the content of such notions as “general principles of international law”, “generally recognized principles of international law”, “basic principles of international law”, “fundamental principles of international law”, “imperative norms of international law”. The author comes to the conclusion that “generally recognized principles of international law” both in the western and in the Russian doctrine of international law presuppose “general principles of international law” or “general principles of law” as a whole with the addition of “civilized nations”, which are often referred to as “fundamental”; these principles include, first of all, the principles enshrined in the UN Charter, the 1970 Declaration on the Principles of International Law and the 1975 Helsinki Final Act of the CSCE. The analysis of practice of international judicial institutions, mainly the International Court of Justice, allows to conclude that the Court does not differentiate the principles which it applies; all of them, as enshrined in the UN Charter, i.e. “generally recognized”, and others (in particular, principles of branches of international law, for example, the principle of humanism) are referred to as “general” principles of law. Moreover, the general principles of law, according to legal doctrine, may cover moral norms, which have been fragmentarily and declaratively already found fixation in international documents, and which in the long term may strengthen their international legal status up to an imperative norm.